Exploring chalcopyrite (bio)leaching mechanisms under thermophilic conditions - Toledo, Ailton Guilherme Rissoni [UNESP]; Costa, Rachel Biancalana; Delforno, Tiago Palladino; Arena, Fabiana Antonia [UNESP]; Bevilaqua, Denise [UNESP] (Elsevier, 2023)
Chalcopyrite is highly recalcitrant to bioleaching and its dissolution mechanisms are still debatable. In this study, both concentrated and low-grade chalcopyrite were subjected to bioleaching using three microbial consortia under thermophilic conditions. Copper extraction efficiency from concentrated chalcopyrite was assessed in Erlenmeyer flasks and reached nearly 90 % in all consortia, whereas it was limited to 30 % in the abiotic control. Results indicate the prevalence of the chalcocite mechanism, in which chalcopyrite is initially reduced to chalcocite followed by its dissolution. This mechanism was enabled by maintaining the solution potential (ES) lower than the Nernst potential (E1), with microbial activity playing an essential role in lowering ES. The most abundant microorganisms were affiliated with primary producers (such as Cyanobacteria) and chemoorganotrophs (such as Bradyrhizobium), contributing to chalcopyrite dissolution indirectly. Microorganisms kept pH within 1.9–2.1, which led to higher Fe3+ precipitation and lower ES. Copper extraction in low-grade ore reactors was assessed in batch system with closed circulation between a five-liter jacketed packed bed reactor and a five-liter buffer vessel, simulating a (bio)leaching heap. Differently from the observed in concentrated ore, copper extraction efficiency from low-grade chalcopyrite was higher in the abiotic control (60 % compared to 40–47 % under biotic conditions). Based on thermodynamic calculations, a new two-step model for ferrous-promoted chalcopyrite leaching was proposed, whereby chalcopyrite is reduced to bornite followed by its fast oxidation. Understanding copper extraction through different routes is crucial for achieving efficient (bio)leaching of chalcopyrite.
Keywords: Bornite; Chalcocite; Extremophilic microorganisms; Low-grade ore; Mineral dissolution; Redox potential